Factors Associated With Exclusive Breastfeeding On The Worker Mother - Yurizki Telova; Damayanti .; Pratiwi Christa Simarmata (JURNAL KEBIDANAN KESTRA (JKK), 2023)
babies are malnourished, development is less than optimal and growth is also not in accordance with age, this study has a goal, namely to find out what are the factors for the failure of Eklsusif breastfeeding, this study used 36 samples of mothers in total sampling using analytical survey crossectional method. The instrument used was a questionnaire sheet while testing with the chi- square test. The results showed that the majority of respondents worked as many as 23 people (63.9%), good knowledge as many as 20 people (55.6%), for a positive attitude as many as 19 people (52.8%), the majority of husband's support supported as many as 20 people (55.6%) the majority of respondents did not provide exclusive breastfeeding as many as 22 people (61.1%). The conclusion of the study shows that there is a relationship between work (0.006), knowledge (0.004), attitude (0.014) husband's support (0.025) with exclusive breastfeeding at Pratama Aulia Medika Clinic, Tualang District, Siak. This study expects mothers who have babies and are working to increase insight and management of exclusive breastfeeding is very important for the growth and development of babies in order to reduce diarrhea, and infections.